2013
DOI: 10.1161/circulationaha.112.115428
|View full text |Cite|
|
Sign up to set email alerts
|

Permanent Cardiac Pacing in Children: Choosing the Optimal Pacing Site

Abstract: Background-We evaluated the effects of the site of ventricular pacing on left ventricular (LV) synchrony and function in children requiring permanent pacing. Methods and Results-One hundred seventy-eight children (aged <18 years) from 21 centers with atrioventricular block and a structurally normal heart undergoing permanent pacing were studied cross-sectionally. Median age at evaluation was 11.2 (interquartile range, 6.3-15.0) years. Median pacing duration was 5.4 (interquartile range, 3.1-8.8) years. Pacing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(98 citation statements)
references
References 37 publications
8
86
0
3
Order By: Relevance
“…While many studies support the notion that LV-only pacing may have beneficial effects in HF patients [26], recent data in children with normal cardiac function and complete AV block demonstrated striking similarity to the results of our rat model in regard to LVonly pacing [27]. Moreover, LV-only pacing appears to be associated with good clinical outcome in this and other studies in the pediatric population [28,29]. It should be mentioned that the segmental findings of our study as well as the pediatric studies stated above appear to contrast the findings of [30], which demonstrated reduced Ecc near the LV pacing site compare to remote sites near the RV in the dog model of acute pacing.…”
Section: Discussionsupporting
confidence: 83%
“…While many studies support the notion that LV-only pacing may have beneficial effects in HF patients [26], recent data in children with normal cardiac function and complete AV block demonstrated striking similarity to the results of our rat model in regard to LVonly pacing [27]. Moreover, LV-only pacing appears to be associated with good clinical outcome in this and other studies in the pediatric population [28,29]. It should be mentioned that the segmental findings of our study as well as the pediatric studies stated above appear to contrast the findings of [30], which demonstrated reduced Ecc near the LV pacing site compare to remote sites near the RV in the dog model of acute pacing.…”
Section: Discussionsupporting
confidence: 83%
“…11, 14 They reported that LVEF was significantly inversely correlated with SPWMD (R 2 =0.454, P<0.001). 11 In the present study, the clinical parameters were the same among patients with RVI, RVA, and LV pacing within 1 year of PMI. These results may be explained by the retrospective study design, which included data from 30 years ago.…”
Section: Pacing Sites and Development Of Dcmmentioning
confidence: 51%
“…16, 17 We used the criteria of Manolio et al 18 for DCM diagnosis and defined DCM as having 117% of the normal LV right bundle branch block morphology was designated as the LV lateral wall or LV base. 11 The pacing sites were classified into 6 segments of RV and 17 segments of LV. To delineate the RV segments, a line was drawn from the membranous septum to the apex to divide the septum into anterior and inferior halves; further subdividing the base to apex length into 3 parts (basal, middle, and apical) provided 6 segments.…”
Section: Clinical Measurementsmentioning
confidence: 99%
“…35 Together with the higher venous occlusion rate in the smallest of infants, our approach has been modified such that, transvenous pacing is no longer first line for patients <5 kg. We now favor placement of steroid-eluting epicardial leads on the left ventricle reserving transvenous pacing with a 4.1F lead for failure of the epicardial system or complications.…”
Section: Current Approachmentioning
confidence: 99%